2017
DOI: 10.3390/polym9090403
|View full text |Cite
|
Sign up to set email alerts
|

Polyol Structure and Ionic Moieties Influence the Hydrolytic Stability and Enzymatic Hydrolysis of Bio-Based 2,5-Furandicarboxylic Acid (FDCA) Copolyesters

Abstract: A series of copolyesters based on furanic acid and sulfonated isophthalic acid with various polyols were synthetized and their susceptibility to enzymatic hydrolysis by cutinase 1 from Thermobifida cellulosilytica (Thc_Cut1) investigated. All copolyesters consisted of 30 mol % 5-sulfoisophthalate units (NaSIP) and 70 mol % 2,5-furandicarboxylic acid (FDCA), while the polyol component was varied, including 1,2-ethanediol, 1,4-butanediol, 1,8-octanediol, diethylene glycol, triethylene glycol, or tetraethylene gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 58 publications
(94 reference statements)
1
12
0
Order By: Relevance
“…This result was consistent with the higher crystallinity of PEF and PLA, which made their ester bonds inaccessible to hydrolysis. Haernvall 135 synthesized a series of furan-based copolyesters with different polyols. Very interestingly, they found that when they replaced the linear diols with branched ones or incorporated ethoxy units into the polymer chain, the enzyme activity was doubled.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This result was consistent with the higher crystallinity of PEF and PLA, which made their ester bonds inaccessible to hydrolysis. Haernvall 135 synthesized a series of furan-based copolyesters with different polyols. Very interestingly, they found that when they replaced the linear diols with branched ones or incorporated ethoxy units into the polymer chain, the enzyme activity was doubled.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Another reason for this large difference in the MW determined by the two techniques was the aggregation characteristics of the polyols. The formation of aggregates resulted in a larger average size of the polyol molecule and was thus detected by GPC as a higher-MW polyol …”
Section: Resultsmentioning
confidence: 99%
“…The formation of aggregates resulted in a larger average size of the polyol molecule and was thus detected by GPC as a higher-MW polyol. 55 3.2. Amination of the Polyester Polyols.…”
Section: Resultsmentioning
confidence: 99%
“…The enzyme Thc_Cut1 is capable of hydrolysing polyesters with a preferred cleavage of ester bonds in the vicinity of the non-charged building blocks. 201 The effect of molecular mass, particle size and crystallinity of the PEF polyester (powders and amorphous lms) on enzymatic hydrolysis was investigated using different cutinases from Thermobida cellulosilytica (Thc_Cut1) and Humicola insolens (HiC). The enzyme Thc_Cut1 efficiently hydrolysed PEF powders with low molecular masses (M n 18 kg mol À1 ) and low crystallinity compared to higher MWs (M n 55 kg mol À1 ) and higher crystallinity.…”
Section: Chemical and Enzymatic Recycling Of Emerging Biopolymersmentioning
confidence: 99%
“…The enzyme Thc_Cut1 is capable of hydrolysing polyesters with a preferred cleavage of ester bonds in the vicinity of the non-charged building blocks. 201 …”
Section: Chemical and Enzymatic Recycling Of Emerging Biopolymersmentioning
confidence: 99%